Autoimmune pancreatitis type 1 and type 2: what we know so far - Piotrowska, Marta; Gmitrzuk, Julita; Malinka, Zuzanna; Wiśniewska, Katarzyna; Jachymek, Anna; Opatowska, Martyna; Jakubiec, Joanna; Kucharski, Tomasz (Quality in Sport, 2024)
Autoimmune pancreatitis (AIP) is a unique form of chronic pancreatitis characterized by lymphoplasmacytic infiltration, pancreatic fibrosis, and responsiveness to steroid therapy. It is classified into two histological subtypes: Type 1 (Lymphoplasmacytic Sclerosing Pancreatitis, LPSP) and Type 2 (Idiopathic Duct-centric Pancreatitis, IDCP). Type 1 AIP, associated with IgG4-related disease, typically affects older males and often involves other organs, whereas Type 2 AIP, more common in younger patients and linked to inflammatory bowel diseases, is limited to the pancreas. Diagnosis, which differentiates AIP from pancreatic cancer, relies on histopathology, imaging, serology, organ involvement, and steroid responsiveness, guided by the Mayo Clinic HISORt and International Consensus Diagnostic Criteria (ICDC). The pathogenesis of AIP involves complex immunological, genetic, and environmental factors, with Type 1 characterized by IgG4-producing plasma cells and Type 2 by granulocytic infiltration. Treatment predominantly involves corticosteroids, effective for both types but with a higher relapse rate in Type 2, necessitating long-term immunosuppressive therapies such as azathioprine, mycophenolate mofetil, and rituximab. Emerging biological therapies targeting specific immune pathways show promise. This review highlights the clinical presentation, diagnostic challenges, pathophysiology, and therapeutic approaches for AIP, emphasizing the need for ongoing research to improve diagnostic accuracy and develop more effective, targeted treatments.